Protein Kinases at the Intersection of Translation and Virulence - Leipheimer, Jay; Bloom, Amanda L. M.; Panepinto, John C. (Frontiers in Cellular and Infection Microbiology, 2019)
As free living organisms, fungi are challenged with a variety of environmental insults that threaten their cellular processes. In some cases, these challenges mimic conditions present within mammals resulting in the accidental selection of virulence factors over evolutionary time. Be it within a host or the soil, fungi must contend with environmental challenges through the production of stress effector proteins while maintaining factors required for viability in any condition. Initiation and upkeep of this balancing act is mainly under the control of kinases that affect the propensity and selectivity of protein translation. This review will focus on kinases in pathogenic fungi that facilitate a virulence phenotype through translational control.